1999
DOI: 10.1093/jnci/91.24.2087
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Expansion and Loss of Heterozygosity at Chromosomes 9p and 17p in Premalignant Esophageal (Barrett's) Tissue

Abstract: LOH at 9p and 17p chromosomes are highly prevalent somatic genetic lesions in premalignant Barrett's tissue. LOH at 9p is more common than LOH at 17p in diploid samples and can be detected over greater regions of Barrett's epithelium. In most patients with high-grade dysplasia, the Barrett's mucosa contains a mosaic of clones and subclones with different patterns of LOH. Some clones had expanded to involve extensive regions of Barrett's epithelium. LOH at 9p and 17p chromosomes may be useful biomarkers to stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
116
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(127 citation statements)
references
References 50 publications
8
116
2
1
Order By: Relevance
“…Barrett's esophagus is recognized as a phenotypically and genotypically heterogeneous structure formed by several distinct genetic clones. [23][24][25][26] This study identified different clones with distinct karyotypes in the same patient confirming this statement and illustrating the chromosomal instability present in Barrett's esophagus even in the absence of dysplasia or cancer. This instability may facilitate the expansion of clones carrying particular abnormalities with selective advantages as has been described for loss of heterozigosity at 17p and 9p.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Barrett's esophagus is recognized as a phenotypically and genotypically heterogeneous structure formed by several distinct genetic clones. [23][24][25][26] This study identified different clones with distinct karyotypes in the same patient confirming this statement and illustrating the chromosomal instability present in Barrett's esophagus even in the absence of dysplasia or cancer. This instability may facilitate the expansion of clones carrying particular abnormalities with selective advantages as has been described for loss of heterozigosity at 17p and 9p.…”
Section: Discussionsupporting
confidence: 72%
“…This instability may facilitate the expansion of clones carrying particular abnormalities with selective advantages as has been described for loss of heterozigosity at 17p and 9p. [23][24][25][26] Conventional cytogenetics has, over other methods of chromosomal analysis, the ability to detect and characterize specific abnormalities. Its widespread routine application on Barrett's esophagus is not feasible mostly due to the difficulties in culturing nonneoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have investigated the role of different oncogenes and tumor suppressor genes in esophageal carcinogenesis (Dolan et al, 1999;Jankowski et al, 1999;Roncalli et al, 1998;Walch et al, 2000;Wu et al, 1998), focusing on the advanced stages of progression from dysplasia to neoplasia, scarce data are available on genetic alterations occurring in Barrett's esophagus in the absence of neoplastic and/or dysplastic changes (Campomenosi et al, 1996;Galipeau et al, 1999 ). Three major histological forms of Barrett's esophagus have been described: a specialized columnar type, a cardiac type, and a fundic type.…”
mentioning
confidence: 99%
“…Loss of heterozygosity of chromosome 17p has been determined to be a marker of Barrett's esophagus progression. 5 A p53 mutation has been shown in the progression of Barrett's esophagus and is the underlying genetic change for loss of heterozygosity in chromosome 17p. 22 Tumor suppressor genes, such as p16, RUNX3, and HPP1 that undergo methylation, have been shown in one study 23 to function as biomarkers for predicting the progression of Barrett's esophagus to adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] This variation is highest between low-grade dysplasia and indefinite for dysplasia and between high-grade dysplasia and early invasive adenocarcinoma. 3 Testing for aneuploidy, tetraploidy, and p16 and p53 genetic abnormalities, such as the loss of heterozygosity of chromosomes 9p and 17p, [5][6][7] have been shown to correlate with the risk of adenocarcinoma, but this is difficult to obtain in routine surgical pathology practice, particularly given the limited amount of tissue available in an endoscopic biopsy sample. Immunohistochemical markers, such as a-methyl coenzyme A racemase (AMACR), p53, caspase 3, and survivin, are promising as ancillary tests to facilitate the grading of dysplasia and to diagnose early adenocarcinoma in Barrett's esophagus.…”
mentioning
confidence: 99%